Non‐Scale Endogenous Growth with R&D and Human Capital. (21st January 2016) - Day, Creina
Abstract: This paper examines the conditions under which increasing knowledge, encapsulated in ideas for new technology through R&D and embodied in human capital through education, sustains economic growth. A general model is developed where, consistent with recent literature, growth is non‐scale (not increasing in population size) and endogenous (generated by factors within R&D and education). Recent models feature the counterfactual assumption of constant returns to existing knowledge and restrict the substitutability of inputs within R&D and education. We find that non‐scale endogenous growth is possible under less stringent conditions. The findings reconcile sustained economic growth with evidence of diminishing marginal returns in education and R&D, which suggests an ambiguous role for R&D policy.